Advanced Photonics 2011
DOI: 10.1364/iprsn.2011.iwe3
|View full text |Cite
|
Sign up to set email alerts
|

Integrated GaN photonic circuits on silicon (100) for second harmonic generation

Abstract: Abstract:We demonstrate second order optical nonlinearity in a silicon architecture through heterogeneous integration of single-crystalline gallium nitride (GaN) on silicon (100) substrates. By engineering GaN microrings for dual resonance around 1560 nm and 780 nm, we achieve efficient, tunable second harmonic generation at 780 nm. The χ (2) nonlinear susceptibility is measured to be as high as 16 ± 7 pm/V. Because GaN has a wideband transparency window covering ultraviolet, visible and infrared wavelengths, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The first one (Approach I) is reported by VicoTrivino et al (2013), where GaN waveguides and photonic crystal cavities are achieved with freestanding structure supported by tethers on silicon (111) substrates. The other one (Approach II) is demonstrated by Xiong et al (2011), where second order optical nonlinearity is demonstrated with integration of single-crystalline GaN on silica with a bonding process. In our simulation, both approaches are considered as the GaN strips are filled with and surrounded by air (refractive index of 1) or silica (refractive index of 1.54).…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one (Approach I) is reported by VicoTrivino et al (2013), where GaN waveguides and photonic crystal cavities are achieved with freestanding structure supported by tethers on silicon (111) substrates. The other one (Approach II) is demonstrated by Xiong et al (2011), where second order optical nonlinearity is demonstrated with integration of single-crystalline GaN on silica with a bonding process. In our simulation, both approaches are considered as the GaN strips are filled with and surrounded by air (refractive index of 1) or silica (refractive index of 1.54).…”
Section: Model and Methodsmentioning
confidence: 99%
“…Actually, GaN waveguide based photonic circuits have been demonstrated to realize photonic crystal cavity (VicoTrivino et al 2013) and second order optical nonlinearity (Xiong et al 2011). However, the operating wavelength in VicoTrivino et al (2013) and Xiong et al (2011) is still 1:5 lm so that the advantage of adopting III-V material is not fully taken especially with III-V emitter. In order to applying the GaN material on LOC operating in visible band, the absorption loss of transmitting lightwave has to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…However Raman scattering over a large bandwidth will accompany pair generation in these amorphous materials which will have to be operated accordingly 5 . The addition of χ (2) materials such as GaN [167] or AlN [106] may also provide the option of using SPDC instead of SFWM to generate photon pairs.…”
Section: B Two-photon Absorptionmentioning
confidence: 99%
“…Second order non-linear optics is a strategic technology for the integration of advanced photonic functions [1] and the development of non-classical light sources for applications in quantum optics [2]. In the recent years, thanks to the strong field confinement into whispering gallery modes (WGM), microring and microdisk resonators proved to be an efficient geometry to achieve frequency conversion in a large panel of materials, from LiNbO 3 [3,4,5,6,7,8] to III-V semiconductors [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The integration of such devices on silicon photonic platforms still remains challenging [10,15] but is particularly relevant with GaP thanks to its quasi-lattice matching with Si. The heteroepitaxial growth of III-V compounds on Si has been studied for years [16,17], and a taxonomy of integration-induced defects has been established [18].…”
Section: Introductionmentioning
confidence: 99%